Cycloheximide-Producing Streptomyces Associated With Xyleborinus saxesenii and Xyleborus affinis Fungus-Farming Ambrosia Beetles - Grubbs, Kirk J.; Surup, Frank; Biedermann, Peter H. W.; McDonald, Bradon R.; Klassen, Jonathan L.; Carlson, Caitlin M.; Clardy, Jon; Currie, Cameron R. (Frontiers in Microbiology, 2020)
Symbiotic microbes help a myriad of insects acquire nutrients. Recent work suggests that insects also frequently associate with actinobacterial symbionts that produce molecules to help defend against parasites and predators. Here we explore a potential association between Actinobacteria and two species of fungus-farming ambrosia beetles, Xyleborinus saxesenii and Xyleborus affinis. We isolated and identified actinobacterial and fungal symbionts from laboratory reared nests, and characterized small molecules produced by the putative actinobacterial symbionts. One 16S rRNA phylotype of Streptomyces (XylebKG-1) was abundantly and consistently isolated from the nests and adults of X. saxesenii and X. affinis nests. In addition to Raffaelea sulphurea, the symbiont that X. saxesenii cultivates, we also repeatedly isolated a strain of Nectria sp. that is an antagonist of this mutualism. Inhibition bioassays between S. griseus XylebKG-1 and the fungal symbionts from X. saxesenii revealed strong inhibitory activity of the actinobacterium towards the fungal antagonist Nectria sp. but not the fungal mutualist R. sulphurea. Bioassay guided HPLC fractionation of S. griseus XylebKG-1 culture extracts, followed by NMR and mass spectrometry identified cycloheximide as the compound responsible for the observed growth inhibition. A biosynthetic gene cluster putatively encoding cycloheximide was also identified in S. griseus XylebKG-1. The consistent isolation of a single 16S phylotype of Streptomyces from two species of ambrosia beetles, and our finding that a representative isolate of this phylotype produces cycloheximide, which inhibits a parasite of the system but not the cultivated fungus, suggests that these actinobacteria may play defensive roles within these systems.